Evaluating the Effectiveness of Social Rehabilitation Programs for Beggars in Batam: Challenges and Strategic Interventions - Mahendra, Ghazal; Lodan, Karol Teovani (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
This study aims to describe the social rehabilitation programs for beggars in Batam, using a qualitative descriptive method. The Batam City Social and Community Empowerment Agency is tasked with addressing this issue through social rehabilitation programs. From 2019 to 2022, the number of beggars in Batam increased from 150 to 190, as per the agency's data. To address this, the agency conducts regular outreach and rehabilitation to help beggars reintegrate into society and cease their street activities. The research explores the implementation of these programs and identifies the challenges they face. Document analysis of journals, books, and other references supplements the qualitative data. The findings highlight the pivotal role of the Batam City Social and Community Empowerment Agency in mitigating social issues and supporting social welfare. The agency's activities include regular raids and rehabilitation programs through the Nilam Suri Social Welfare Service Center (P2MKS).